2020
DOI: 10.3390/polym12061314
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of Lanthanoid-Poly(Sodium Acrylate) Composites: Insights on the Interaction Mechanism

Abstract: The interaction between polyelectrolytes and metal ions is governed by different types of interactions, leading to the formation of different phases, from liquid state to weak gels, through an appropriate choice of metal ion/polyelectrolyte molar ratio. We have found that lanthanide ions, europium(III) and terbium(III), are able to form polymer composites with poly(sodium acrylate). That interaction enhances the luminescent properties of europium(III) and terbium(III), showing that Eu3+/poly(sodium acrylate) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It is well-known that certain metal ions quench the luminescence of lanthanide ions in polymeric matrices. Studies with Eu(III)/PSA and Tb(III)/PSA have already been reported [ 5 ], and Cu(II) was the cation accounting for the highest suppression of luminescence in both cases.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…It is well-known that certain metal ions quench the luminescence of lanthanide ions in polymeric matrices. Studies with Eu(III)/PSA and Tb(III)/PSA have already been reported [ 5 ], and Cu(II) was the cation accounting for the highest suppression of luminescence in both cases.…”
Section: Resultsmentioning
confidence: 83%
“…336 nm and 348 nm, owing to Phen-to-metal energy transfer, along with some characteristic absorption bands that allow us to distinguish Eu(III)-based from Tb(III)-based complexes ( Figure S1 ). Excitation spectra of Eu(III)/PSA and Tb(III)/PSA can be found elsewhere [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The broad band in the range of 230–300 nm in the excitation spectrum results from the O 2− → Eu 3+ charge transfer and π–π* electronic transition in coordinated organic ligands [ 30 , 31 , 32 ]. As shown in Figure 3 a and Supplementary Figure S3 , the emission spectra exhibit five characteristic transitions of Eu 3+ centered at 579, 591, 615, 651, and 699 nm, corresponding to the 5 D 0 → 7 F J transitions ( J = 0, 1, 2, 3, and 4), respectively [ 33 ].…”
Section: Resultsmentioning
confidence: 99%